Hospital Acquired Pneumonia Due to Achromobacter spp. in a Geriatric Ward in China: Clinical Characteristic, Genome Variability, Biofilm Production, Antibiotic Resistance and Integron in Isolated Strains - Liu, Chao; Pan, Fei; Guo, Jun; Yan, Weifeng; Jin, Yi; Liu, Changting; Qin, Long; Fang, Xiangqun (Frontiers in Microbiology, 2016)
Background: Hospital-acquired pneumonia (HAP) due to Achromobacter has become a substantial concern in recent years. However, HAP due to Achromobacter in the elderly is rare. Methods: A retrospective analysis was performed on 15 elderly patients with HAP due to Achromobacter spp., in which the sequence types (STs), integrons, biofilm production and antibiotic resistance of the Achromobacter spp. were examined. Results: The mean age of the 15 elderly patients was 88.8±5.4 years. All patients had at least 3 underlying diseases and catheters. Clinical outcomes improved in 10 of the 15 patients after antibiotic and/or mechanical ventilation treatment, but three patients had chronic infections lasting more than 1 year. The mortality rate was 33.3% (5/15). All strains were resistant to aminoglycosides, aztreonam, nitrofurantoin, and third- and fourth-generation cephalosporins (except ceftazidime and cefoperazone). Six new STs were detected. The most frequent ST was ST306. ST5 was identified in two separate buildings of the hospital. ST313 showed higher MIC in cephalosporins, quinolones and carbapenems, which should be more closely considered in clinical practice. All strains produced biofilm and had integron I and blaOXA-114-like. The main type was blaOXA-114q. The variable region of integron I was different among strains, and the resistance gene of the aminoglycosides was most commonly inserted in integron I. Additionally, blaPSE-1 was first reported in this isolate. Conclusion: Achromobacter spp. infection often occurs in severely ill elders with underlying diseases. The variable region of integrons differs, suggesting that Achromobacter spp. is a reservoir of various resistance genes.